Crystallization behavior and properties of a novel rare-earth rich BaO–SiO2–La2O3 glass-ceramic for millimeter-wave technology. Issue 19 (1st October 2022) - Yang, Yanguo; Ren, Haishen; Peng, Haiyi; Xie, Tianyi; Zhang, Yi; He, Fei; Lin, Huixing
Abstract: In this work, a novel low permittivity and high expansion coefficient rare-earth rich BaO–SiO2 –La2 O3 (BSL) glass-ceramic for millimeter-wave technology was systematically investigated by the network structure, crystallization the phase transformation, microstructure and microwave dielectric properties. With the decrease of the SiO2 /BaO mol ratio from 3.75 to 0.9, the crystallization activation energy (Ec ) of BSL glass calculated by the Kissiger equation continued to fall from 400.65 to 316.85 kJ/mol, and the crystal growth mode of all samples judging by Avrami parameter (n) was 1-D volume crystallization, implying that the crystallization ability of the BSL glass was enhanced. The main crystal phase of BSL glass-ceramic transformed from BaSi2 O5 to BaSiO3 phase, coincided with a second phase Ba4 La6 O(SiO4 )6 . And then, the relative permittivity ε r of BSL glass-ceramic had increased from 7.8 to 11, while quality factor (Q × f), temperature coefficient of frequency τ f, and coefficient of thermal expansion (CTE) had decreased with the decrease of SiO2 /BaO ratio. By adjusting the mol ratio of SiO2 /BaO, the best comprehensive properties of 20BaO–75SiO2 –5La2 O3 glass-ceramic could be obtained with ε r = 7.8, Q × f = 21000 GHz, CTE = 12.39 × 10 −6 /°C (30–800 °C), which was favorable properties for microwave dielectric applications.